Si-Accumulation In Artemisia annua Glandular Trichomes Increases Artemisinin Concentration, but Does Not Interfere In the Impairment of Toxoplasma gondii Growth - Rostkowska, Cristina; Mota, Caroline M.; Oliveira, Taísa C.; Santiago, Fernanda M.; Oliveira, Lilian A.; Korndörfer, Gaspar H.; Lana, Regina M. Q.; Rossi, Monica L.; Nogueira, Neusa L.; Simonnet, Xavier; Mineo, Tiago W. P.; Silva, Deise A.O.; et al. (Frontiers in Plant Science, 2016)
Artemisia annua is used as a source of artemisinin, a potent therapeutic agent used for the treatment of infectious diseases, chiefly malaria. However, the low concentration (from 0.01 to 1.4% of dried leaf matter) of artemisinin in the plant obtained with the traditional cropping system makes it a relatively expensive drug, especially in developing countries. Considering that artemisinin and silicon (Si) are both stored in A. annua glandular trichomes, and that Si accumulation has never been investigated, this study aimed to look into Si effects on A. annua trichome artemisinin concentration, and whether leaf infusion from Si-treated A. annua plants is able to control Toxoplasma gondii growth. T. gondii is the etiologic agent of toxoplasmosis, a zoonotic parasitic disease whose traditional treatment shows significant side effects. The experimental design consisted of A. annua seedlings randomly planted in soil treated with different doses of calcium/magnesium silicate (0, 200, 400, 800, and 1600 kg ha-1). Analysis of foliar macronutrients showed significant increases of nitrogen content only at the highest dose of silicate. Foliar micronutrients, Si concentrations, and plant height were not affected by any of the silicate doses. However, the dose of 400 kg ha-1 of silicate increased the trichome size, which in turn raised artemisinin concentration in leaves and the infusion. In contrast, the 800 and 1600 kg ha-1 doses dramatically decreased artemisinin concentration. HeLa cell treatment with the infusion of A. annua grown in soil treated with 400 kg ha-1 of silicate decreased parasite proliferation in a dose-dependent manner when the treatment was carried out after or along with T. gondii infection. However, this effect was similar to A. annua grown in soil without silicate treatment. Thus, it can be concluded that, even though Si applied to the soil at 400 kg ha-1 has a positive effect on the A. annua glandular trichome size and the artemisinin concentration, this outcome cannot be directly associated with the efficiency of A. annua infusion on T. gondii growth, suggesting that other components from A. annua leaves could be acting in synergy with artemisinin.